Impact of deboronation on the electronic characteristics of closo-o-carborane: intriguing photophysical changes in triazole-appended carboranyl luminophores. Issue 9 (12th February 2021) - Kim, Mingi; Im, Sehee; Ryu, Chan Hee; Lee, Seok Ho; Hong, Ju Hyun; Lee, Kang Mun
Abstract : A deboronation reaction of 1, 2, 4-triazole-appended closo-o -carboranyl luminophores to nido-o -carboranes results in a ratiometric change in the emission color from deep-blue to sky-blue, in addition to intense turn-on responses. Abstract : 5-Phenyl-1, 2, 4-triazole-appended closo - (CB1 and CB2 ) and nido-o -carboranyl ( nido -CB1 and nido -CB2 ) compounds were prepared and fully characterized using multinuclear NMR spectroscopy and elemental analysis. The solid-state molecular structures of both closo -compounds were analyzed by X-ray crystallography. Although the closo -compounds exhibited dual emissive patterns in the rigid state (in THF at 77 K), which were assignable to a π–π* local excitation (LE)-based emission ( λ em = ca . 380 nm) on the triazole moieties and to an intramolecular charge transfer (ICT)-based emission ( ca . 460 nm) in which the o -carborane units acted as the acceptor (A), at 298 K in THF, the LE-based emission dominated. In contrast, the nido -compounds exhibited an intensive emission originating from ICT transitions in which the o -carborane units reversibly acted as the donor (D). In particular, the positive solvatochromic effects of both nido -compounds and the results of theoretical calculations for the o -carboranyl compounds supported the electronic role of the o -carboranyl unit in each compound. Investigation of the radiative decay mechanism of the closo - and nido -compounds using their quantum efficiency ( Φ em ) and decay lifetime ( τ obs ) suggested that the ICT-based radiative decay of nido -compounds occurred more efficiently than the LE-based decay of closo -compounds. These results implied that emission from the closo -compounds was drastically enhanced by the deboronation reaction upon exposure to an increasing concentration of fluoride anions, and finally became similar to the emission color (sky-blue) of the nido -compounds.